A New Perspective in the Middle East: a Comprehensive Approach To The Us-Iran Relations in the Region (Glocalism: Journal of Culture, Politics and Innovation, 2016)
This paper discusses the significance of the cooperation between the United States and Iran for the Middle East region. It will be argued that despite the political and ideological conflicts between the U.S. and Iran, reaching a “point by point” agreement would best help to resolve Middle East predicaments, especially the Islamic terrorism. To achieve this, the following pages examine the historical background of issues such as terrorism in the Middle East. This paper also focuses on two main paths to support the better U.S.-Iran cooperation, if not talking about relations at all. First, the theory of “point by point” approach helps both countries to tackle tough agendas and overcome the predicaments in the Middle East. Second, to reach the desired cooperation between these two countries, both the U.S. and Iran need to overcome their own internal constraints as well as the external constrains imposed by other countries. This paper takes an historical and theoretical approach to reveal the two countries’ common interests in the Middle East. The general thesis argues that the Middle East’s security requires the United States and Iran to develop a diplomatic and military cooperation.
Keywords: Middle East; United States; Iran; Nuclear Deal; Islamic State